VIEWERSHIP AND CREDIBILITY OF News MAINSTREAM AND SOCIAL MEDIA: AN ANALYSIS OF PUBLIC PERCEPTION OFDISTRICT BAHAWALPUR - Mahar Muhammad Ahmad Afzal; Dr. Tanveer Hussain; Dr.Nasim Ishaq (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
The study has been designed to check Mainstream media is mostly used by the audience in order to access news information while social media is mostly accessed to get social news information. The main aim of the study factor influences the perception of media credibility to decipher how respondents perceive the news of mainstream media and social media in terms of credibility for news information. A survey with four tehsil and conducted to determine the factors that influence their perception towards mainstream and social media. The systematic sampling method was used to select for inclusion in the sample. The results of the study revealed that mainstream media is more credible than social media to convey news. This study also explored a positive and significant relationship between issue salience, media reliance, and media usage with perception of the social media and mainstream media credibility. Moreover, the study found that male members prefer more mainstream media and female members have their tilt towards social media. Present study proved beneficial for the researchers in the field of media studies. However, the audience from urban and rural areas, was not discussed in the present study therefore, it is recommended that another study can be conducted to fill the research gap.